2020
DOI: 10.3390/diagnostics10100775
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Nucleic Acid (PNA)-Enhanced Specificity of a Dual-Target Real-Time Quantitative Polymerase Chain Reaction (RT-qPCR) Assay for the Detection and Differentiation of SARS-CoV-2 from Related Viruses

Abstract: The threat posed by coronaviruses to human health has necessitated the development of a highly specific and sensitive viral detection method that could differentiate between the currently circulating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and other SARS-related coronaviruses (SARSr-CoVs). In this study, we developed a peptide nucleic acid (PNA)-based real-time quantitative polymerase chain reaction (RT-qPCR) assay targeting the N gene to efficiently discriminate SARS-CoV-2 from other SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To overcome those issues, we applied dual-labeled PNA as a detection probe in LAMP reaction for fluorescence detection of the amplification product in a real-time manner. PNA has been reported that having superior specificity against its template nucleic acid with its neutrally charged peptide backbone nature which does not have a nonspecific binding affinity with minus charged natural phosphate backbone of the template nucleic acid 22,32 . The un-cleavable peptide backbone also reduces the risk of non-specific signal production as a result of thermal degradation during long-term incubation at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome those issues, we applied dual-labeled PNA as a detection probe in LAMP reaction for fluorescence detection of the amplification product in a real-time manner. PNA has been reported that having superior specificity against its template nucleic acid with its neutrally charged peptide backbone nature which does not have a nonspecific binding affinity with minus charged natural phosphate backbone of the template nucleic acid 22,32 . The un-cleavable peptide backbone also reduces the risk of non-specific signal production as a result of thermal degradation during long-term incubation at elevated temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…A unique application incorporating PNAs has recently utilized the hybridization capabilities of the synthesized PNAs as a blocking mechanism to measure human SARS‐CoV‐2 specific gene sequences more sensitively, as compared to bat and other SARS‐related coronaviruses through the conserved sequences of ORF3ab E‐and N‐genes. [ 148 ] This blocking technique aimed to discriminate between SARS‐CoV‐2 and other SARS related‐CoVs in human samples without compromising sensitivity. The sensitivities were significantly increased in both detections when the designed PNAs probe was combined with an RT‐qPCR workflow.…”
Section: Biosensors For the Detection Of Viral Infectionsmentioning
confidence: 99%
“…Lately, many efforts have been directed towards understanding their potential in nucleic acid‐based diagnostics. [ 148,156–158 ]…”
Section: Biosensors For the Detection Of Viral Infectionsmentioning
confidence: 99%
“…The rigid D-prolyl-2-aminocyclopentanecarboxylic acid (ACPC) backbone [ 21 ] of acpcPNA leads to the stronger binding affinity and sequence specificity toward DNA compared to many systems including the original PNA [ 22 ]. Given the benefits of PNA probe over conventional oligonucleotide probes, it has been used as a probe for RT-LAMP [ 23 ] and RT-PCR [ 24 ] with colorimetric assay for highly specific determination of SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%